2014
DOI: 10.3389/fpsyt.2014.00061
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Deeply Encoded Items Memorable? Insights into the Levels of Processing Framework from Neuroimaging and Neuromodulation

Abstract: When we form new memories, their mnestic fate largely depends upon the cognitive operations set in train during encoding. A typical observation in experimental as well as everyday life settings is that if we learn an item using semantic or “deep” operations, such as attending to its meaning, memory will be better than if we learn the same item using more “shallow” operations, such as attending to its structural features. In the psychological literature, this phenomenon has been conceptualized within the “level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 89 publications
0
26
0
1
Order By: Relevance
“…A discrepancy exists however between fMRI and TMS studies. fMRI studies have consistently shown an engagement of the left VLPFC, especially when the encoding task involves semantic processing (Fletcher, Shallice & Dolan, 1998;Blumenfeld & Ranganath, 2007;Galli, 2014), whereas only few studies reported DLPFC activations (Savage et al, 2001;Blumenfeld & Ranganath, 2006). On the contrary, most TMS and tDCS studies of episodic memory found an effect of left DLPFC stimulation on subsequent retrieval (Rossi et al, 2001(Rossi et al, , 2004(Rossi et al, , 2006(Rossi et al, , 2011Epstein, Sekino, Yamaguchi, Kamiya & Ueno, 2002;Sandrini, Cappa, Rossi, Rossini & Miniussi, 2003;Skrdlantová et al, 2005;Turriziani et al, 2008;Turriziani, Smirni, Oliveri, Semenza & Cipolotti, 2010;Elmer, Burkard, Renz, Meyer & Jancke, 2009;Gagnon, Schneider, Grondin & Blanchet, 2010;Innocenti et al, 2010;Javadi, Cheng & Walsh, 2012;Javadi & Cheng, 2013;Manenti, Brambilla, Petesi, Ferrari & Cotelli, 2013) whereas only a few targeted the left VLPFC (Floel et al, 2004;Köhler et al, 2004;Kahn et al, 2005;Machizawa et al, 2010;Blumenfeld et al, 2014;Vidal-Pinero et al, 2014).…”
mentioning
confidence: 99%
“…A discrepancy exists however between fMRI and TMS studies. fMRI studies have consistently shown an engagement of the left VLPFC, especially when the encoding task involves semantic processing (Fletcher, Shallice & Dolan, 1998;Blumenfeld & Ranganath, 2007;Galli, 2014), whereas only few studies reported DLPFC activations (Savage et al, 2001;Blumenfeld & Ranganath, 2006). On the contrary, most TMS and tDCS studies of episodic memory found an effect of left DLPFC stimulation on subsequent retrieval (Rossi et al, 2001(Rossi et al, , 2004(Rossi et al, , 2006(Rossi et al, , 2011Epstein, Sekino, Yamaguchi, Kamiya & Ueno, 2002;Sandrini, Cappa, Rossi, Rossini & Miniussi, 2003;Skrdlantová et al, 2005;Turriziani et al, 2008;Turriziani, Smirni, Oliveri, Semenza & Cipolotti, 2010;Elmer, Burkard, Renz, Meyer & Jancke, 2009;Gagnon, Schneider, Grondin & Blanchet, 2010;Innocenti et al, 2010;Javadi, Cheng & Walsh, 2012;Javadi & Cheng, 2013;Manenti, Brambilla, Petesi, Ferrari & Cotelli, 2013) whereas only a few targeted the left VLPFC (Floel et al, 2004;Köhler et al, 2004;Kahn et al, 2005;Machizawa et al, 2010;Blumenfeld et al, 2014;Vidal-Pinero et al, 2014).…”
mentioning
confidence: 99%
“…Concerning the type of deep and surface processing, a variety of encoding tasks were defined in these studies (Table ). Following the systematic review of Galli (), these encoding tasks can be ordered along a semantic‐structural axis. Deep levels of processing fall under the semantic part and surface levels of processing under the structural part, but some tasks are located at the intermediate level along the semantic‐structural axis (Galli, ).…”
Section: Resultsmentioning
confidence: 99%
“…Following the systematic review of Galli (), these encoding tasks can be ordered along a semantic‐structural axis. Deep levels of processing fall under the semantic part and surface levels of processing under the structural part, but some tasks are located at the intermediate level along the semantic‐structural axis (Galli, ). With regard to deep levels of processing, previous reviews indicated that animacy judgment tasks need a semantic analysis (Binder, Desai, Graves, & Conant, ; Galli, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations